PERBEDAAN RERATA KADAR AKTIVIN A SERUM MATERNAL ANTARA PREEKLAMSIA BERAT DENGAN BUKAN PREEKLAMSIA BERAT - Dovy Djanas; Bayu Pramudyo Ariwibowo; Hafni Bachtiar (Universitas Andalas, 2019)
At the start of preelampsia there is a failure of cytotrophoblst invasion into the maternal spiral arteries that will lead to decreased uteroplacetal perfusion which will be followed by the failure of the unit fetoplacenter to get enough oxygen from the room intervillous that ultimately lead to a state of hypoxia in placenta. This will cause the expenditure of TNF-α dan IL-1β from placenta and a factors called hypoxia-inducible transcription factors that will spur the trophoblast to produce activin A lot more. This research was conducted by cross sectional method in maternal room of obstetrics and gynecology department of Central General Hospital of Dr. M. Djamil Padang from August 2015 until February 2016 with 20 patients of severe preeclampsia and 20 patients not severe preeclampsia, who met inclusion criteria and there is no exclusion criteria. Then performed statistical analysis using Mann-Whitney test to determine difference in mean maternal activin A serum levels of severe preeclampsia and not severe preeclampsia. The mean maternal serum levels of activin A in severe preeclampsia is 32,55 ± 1,84 ng/ml and in pregnancy with no severe preeclampsia is 8,59 ± 0,59 ng/ ml. Difference in mean maternal serum level of activin A in the two groups was statistically significant (p=0,001). Ma-ternal serum activin A levels is significantly higher in severe preeclampsia than pregnancy with no severe preeclampsia.Keywords: Activin A, severe preeclampsia, not severe preeclampsia